The Roles of Unfolded Protein Response Pathways in Chlamydia Pathogenesis. (8th December 2016) - George, Zenas; Omosun, Yusuf; Azenabor, Anthony A; Partin, James; Joseph, Kahaliah; Ellerson, Debra; He, Qing; Eko, Francis; Bandea, Claudiu; Svoboda, Pavel; Pohl, Jan; Black, Carolyn M; et al.
Abstract: Chlamydia is an obligate intracellular bacterium that relies on host cells for essential nutrients and adenosine triphosphate (ATP) for a productive infection. Although the unfolded protein response (UPR) plays a major role in certain microbial infectivity, its role in chlamydial pathogenesis is unknown. We hypothesized that Chlamydia induces UPR and exploits it to upregulate host cell uptake and metabolism of glucose, production of ATP, phospholipids, and other molecules required for its replicative development and host survival. Using a combination of biochemical and pathway inhibition assays, we showed that the 3 UPR pathway transducers—protein kinase RNA-activated (PKR)-like ER kinase (PERK), inositol-requiring enzyme-1α (IRE1α), and activating transcription factor-6α (ATF6α)—were activated during Chlamydia infection. The kinase activity of PERK and ribonuclease (RNase) of IRE1α mediated the upregulation of hexokinase II and production of ATP via substrate-level phosphorylation. In addition, the activation of PERK and IRE1α promoted autophagy formation and apoptosis resistance for host survival. Moreover, the activation of IRE1α resulted in the generation of spliced X-box binding protein 1 (sXBP1) and upregulation of lipid production. The vital role of UPR pathways in Chlamydia development and pathogenesis could lead to the identification of potential molecular targets for therapeutics against Chlamydia .